Single‐Source Precursor Route for Synthesis of High‐Quality Green‐emitting Quantum Dots and Their Hydrophilic Surface Modification. (8th June 2017) - Wang, Sheng; Lv, Yanbing; Wu, Ruili; Li, Lin Song; Shen, Huaibin; Xing, Ming; Chen, Xia
Abstract : The high‐quality green‐emitting CdS0 . 5 Se0 .5 /8Zn1 − x Cd x S/2ZnS QDs with "8" and "2" monolayers (ML) of corresponding shell were first synthesized by "thermal‐cycling coupled single precursor" (TC‐SP) approach. The component‐gradient Zn1− x Cd x S interlayer played a key role in the growth of thick shell by gradually buffering the large lattice mismatch ( 9%) between the CdS0 . 5 Se0 .5 core and ZnS shell. Moreover, the Zn1− x Cd x S gradient interlayer as well as ZnS outshell increased the potential barrier to prevent excitons from being trapped by surface defects. The photoluminescence quantum yields of the as‐synthesized CdS0 . 5 Se0 .5 /8Zn1 − x Cd x S/2ZnS core/shell QDs can reach to 70% in organic media and still maintain 60% after aqueous phase transfer. The green‐emitting CdS0 . 5 Se0 .5 /8Zn1 − x Cd x S/2ZnS core/shell QDs may be good candidates for applications of biomedical and photoelectric field. Abstract :